DIGITAL ENTREPRENEURSHIP THROUGH THE PRISM OF STUDENT ATTITUDES: CHALLENGES AND OPPORTUNITIES - Tripković, Anđelka; Aleksić, Ivana (Economic Outlook, 2024)
The paper analyzes students' attitudes towards digital entrepreneurship, as well as their readiness for active participation in the digital economy. The research was conducted at the University of Prishtina with temporary headquarters in Kosovska Mitrovica, with the aim of determining the level of knowledge of the concept of digital entrepreneurship among students, their motivation for starting their own business, as well as the key skills that are considered important for success in this field. The results show that most students recognize the benefits of digital entrepreneurship, including flexibility and global reach, but at the same time cite lack of experience and the need for education as key challenges. The conducted research provides insight into young people's perceptions of digital entrepreneurship and indicates potential measures that could encourage their engagement in the digital economy.